(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
In 2018, a full-scale reform of general secondary education called “The New Ukrainian School” was launched in Ukraine. The reform will continue until 2029 and aims to update educational content to develop students' competencies and cross-cutting skills necessary for successful personal and professional realization; employ active learning methods; create an innovative and inclusive educational environment; and enhance preparation for future professional and educational trajectories. In this context, pedagogical science and practice face a number of complex and responsible tasks related to the implementation of effective learning models that extensively use digital and interactive technologies, ensuring the formation of lifelong learning competencies (Recommendations of the European Parliament and the Council of the European Union). An important tool for effective learning is an interactive electronic textbook application, which significantly expands the capabilities of a printed textbook through multimedia content and interactive functions. The development of such an application requires not only compliance with the current regulatory framework of Ukraine but also an examination of best practices in the use of electronic textbook applications in the educational theory and practice of European countries. This article is written by the authors of school textbooks for the integrated course "Health, Safety, and Well-Being" for the 7th and 8th grades of the New Ukrainian School. The aim of our study is to theoretically justify and empirically examine the functionality and content fullness of the interactive electronic application to the "Health, Safety, and Well-Being" textbook. The theoretical and experimental study was conducted during 2023-2024 in general secondary education institutions in Ukraine that used the authors' textbook in the educational process. The study involved 600 respondents – school teachers. Our research addressed three main objectives: 1) to analyse the experience of European countries in developing and implementing interactive electronic textbook applications to integrate best practices into the Ukrainian educational space; 2) to conduct a pilot implementation of the interactive electronic application developed by the authors; 3) to identify the factors and conditions that enhance the effectiveness of using an interactive electronic textbook application. The article describes the stages of the research, provides an analysis of the best European practices in using electronic applications to school textbooks, and presents the interactive electronic application developed as a result of this study for the "Health, Safety, and Well-Being" integrated course for the 7th and 8th grades of the New Ukrainian School. The article also includes an analysis of empirical data obtained during the research.